Effects of Aerobic Exercises on Patients With Coronary Artery Disease - Farhad Rahmani-Nia; Arash Layegh; Naser Aslanabadi (Sport Sciences and Health Research)
Introduction: Prescribing the Adrenergic beta-Antagonists is very common in treating cardiovascular diseases. The aim of this study was to compare the effects of aerobic training in patients with coronary artery disease, prescribed two different types of beta-blockers (selective and non- selective) on the patient's lipid profile (Lipoproteins) and FBS (Blood Glucose).Materials and Methods: Sixty patients with coronary artery disease, aged 45-65 years, were compared in two groups of selective (n=36) and non-selective (n=24) users of beta-blockers. The training program consisted of 8 weeks of aerobic exercise on the treadmill (3 sessions per week, about 50 minutes per session, with an intensity of 40% to 60% of the heart rate reserve). Each study patient’s lipid profile and FBS level were obtained before the onset of the study and after the end of the intervention. The collected data were analyzed using repeated-measures Analysis of Variance (ANOVA).Results: In the selective group, lipid profile and FBS did not significantly change. In the non-selective group, FBS and triglyceride levels were significantly reduced after the intervention; however, HDL, LDL, and total cholesterol levels were not significantly changed (P>0.05).Conclusion: The results of this study showed that aerobic training in patients with CAD who used non-selective beta-blockers has more positive effects.